Intellectual impairment in chronic renal failure. Issue 6117 (8th April 1978) - English, A; Savage, R D; Britton, P G; Ward, M K; Kerr, D N
Abstract : In a dialysis centre with a high tap water aluminium content and a known high incidence of dialysis encephalopathy, 29 patients undertaking regular home dialysis, without clinical evidence of encephalopathy, were studied with a battery of psychological tests that have proved useful in detecting early organic intellectual deterioration in other conditions. Full-scale intelligence quotient, as measured by the Wechsler Adult Intelligence Scale, did not differ significantly from that of the normal population, but the patients showed significant deficiencies in three tests of performance–namely, digit symbol, block design, and picture arrangement. The ability to acquire new information in relation to performance was impaired and the abnormality increased with time on dialysis. Such tests should be useful in early detection of dialysis dementia at a reversible stage.